2012
DOI: 10.1515/lp-2012-0020
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acoustically reduced words in spontaneous speech: The role of semantic/syntactic and acoustic cues in context

Abstract: In spontaneous speech, words may be realised shorter than in formal speech (e.g., English yesterday may be pronounced like [ jɛʃeɩ]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…Especially under conditions in which the speech stream does not provide reliable cues, contextual cues become an important source of information for identifying the words and segments of speech. This has been demonstrated by studies investigating the recognition of acoustically reduced speech (e.g., Brouwer, Mitterer, & Huettig, 2012b;Ernestus, Baayen, & Schreuder, 2002;Janse & Ernestus, 2011;van de Ven, Ernestus, & Schreuder, 2012). For example, Ernestus et al (2002) presented strongly reduced word forms extracted from a corpus of spontaneous Dutch either in isolation or in context.…”
Section: Introductionmentioning
confidence: 90%
“…Especially under conditions in which the speech stream does not provide reliable cues, contextual cues become an important source of information for identifying the words and segments of speech. This has been demonstrated by studies investigating the recognition of acoustically reduced speech (e.g., Brouwer, Mitterer, & Huettig, 2012b;Ernestus, Baayen, & Schreuder, 2002;Janse & Ernestus, 2011;van de Ven, Ernestus, & Schreuder, 2012). For example, Ernestus et al (2002) presented strongly reduced word forms extracted from a corpus of spontaneous Dutch either in isolation or in context.…”
Section: Introductionmentioning
confidence: 90%
“…Janse & Ernestus, 2011) to semantic information (e.g. van de Ven, Ernestus, & Schreuder, 2012). If this information is available, as is the case in natural conversations, listeners may process reduced forms as easily as full forms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mattys and colleagues (2005) proposed a model in which the information integrated in lexical processing was hierarchically organized into Btiers,^with knowledgebased factors such as structural (syntactic and semantic) and lexical knowledge comprising the most important sources of information. However, other lines of research have demonstrated that acoustic information strongly influences lexical recognition, especially for reduced word forms in casual speech (e.g., Ernestus, Baayen, & Schreuder, 2002); in fact, when syntactic and lexical cues conflicted with acoustic information, recognition was affected more by acoustic cues than structural cues (Van De Ven, Ernestus, & Schreuder, 2012). These findings are in line with Mattys and colleagues' postulation in a revision of their model that a strictly hierarchical organization cannot account for changes in sensitivity to both acoustic and syntactic information in the speech context Mattys, Melhorn, & White, 2007).…”
mentioning
confidence: 99%